Accountability for the Rights of People with Psychosocial Disabilities: An Assessment of Country Reports for the Convention on the Rights of Persons with Disabilities - Julian Eaton; Aleisha Carroll; Nathaniel Scherer; Lucy Daniel; Michael Njenga; Charlene Sunkel; Kirsty Thompson; Diane Kingston; Gulshan Ara Khanom; Sean Dryer (Harvard FXB Center for Health and Human Rights, 2020)
The Convention on the Rights of Persons with Disabilities (CRPD) has been identified as a milestone in human rights protection, offering people with psychosocial disabilities the opportunity to hold their governments accountable for the realization of their rights. To facilitate such accountability, the country reports produced under the CRPD reporting process should adequately reflect these persons' experiences and relevant positive or negative developments in the country. Our study used content analysis to review the extent and quality of reporting related to mental health and psychosocial disabilities in 19 country reports. The criteria used were based on provisions of the CRPD and on priorities identified by a steering committee of people with psychosocial disabilities. We found a wide variation in the quantity and quality of states' reporting, with an indication that this variation relates to countries' economic development. Increasing the participation of representative organizations of people with psychosocial disabilities is needed for state parties to fulfill their reporting obligations. While there has been progress in improving organizations of persons with disabilities capacity to be heard at the global level, our findings suggest low levels of participation in CRPD processes at the national level in many countries. State parties must actively include these groups to ensure implementation of the CRPD principles.